2017
DOI: 10.1136/annrheumdis-2017-211138
|View full text |Cite
|
Sign up to set email alerts
|

A population-based cohort study of rheumatoid arthritis-associated interstitial lung disease: comorbidity and mortality

Abstract: ILD is a serious complication in RA, with a significantly increased mortality compared with a large matched cohort of RA comparisons without ILD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
216
4
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 326 publications
(247 citation statements)
references
References 44 publications
13
216
4
14
Order By: Relevance
“…This also suggests that articular and pulmonary inflammation may be intrinsically related (28,29). Similar to results of previous studies (1,2,4,13,(30)(31)(32)(33), we observed high mortality rates in patients who developed RA-ILD. More than one-third of patients with RA-ILD died by the end of the follow-up period.…”
Section: Discussionsupporting
confidence: 90%
“…This also suggests that articular and pulmonary inflammation may be intrinsically related (28,29). Similar to results of previous studies (1,2,4,13,(30)(31)(32)(33), we observed high mortality rates in patients who developed RA-ILD. More than one-third of patients with RA-ILD died by the end of the follow-up period.…”
Section: Discussionsupporting
confidence: 90%
“…Under the age of 75 years, incidence rates of RA are up to four times higher in women than men. Fibrosing ILD, the most common pulmonary manifestation of disease (occurring in ∼10% of patients), is a major cause of morbidity and mortality in patients with RA and in some cases can be the first symptom of RA [49,[59][60][61]. RA-ILD is believed to be caused by chronic immune activation and inflammation, which stimulates fibroproliferation in the lung parenchyma of genetically susceptible individuals.…”
Section: Ctd-ildmentioning
confidence: 99%
“…In some cases, lung manifestations may precede the diagnosis of RA. Patients with idiopathic interstitial lung disease should be observed prospectively for signs of systemic disease [3,67,68]. Differential diagnostic considerations should also be part of the follow up and not only of the initial diagnostic work up.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…The lung is a common site of extra-articular disease. Rheumatoid arthritis-associated interstitial lung disease (RA-ILD) is one of the most feared manifestations and causes serious morbidity and increased mortality [1][2][3]. Rheumatoid arthritis is the most common of the connective tissue diseases, and a substantial number of patients with RA will consult general practitioners, rheumatologists, and pulmonologists with respiratory symptoms which, in some cases, may be caused by ILD.…”
Section: Introductionmentioning
confidence: 99%